Late-onset Dysphagia in A Patient With a Discectomy and Anterior Cervical Fusion (Revista de Medicina Clinica, 2020)
Clinical snapshot of a patient with late dysphagia associated with cervical spine surgery.
Keywords: Disphagia; Discectomy; Cervical anterior Fussion